2019
DOI: 10.1111/bjd.17818
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the management of actinic keratosis: a qualitative interview study among general practitioners and dermatologists

Abstract: SummaryBackgroundThe increasing incidence of actinic keratosis (AK) is causing a large burden on healthcare systems. The current management of patients with AK seems to vary within and between primary and secondary care; however, an in‐depth understanding of healthcare providers’ management of AK is currently lacking.ObjectivesTo gain insight into the management of AK by exploring the underlying motives of current practices among general practitioners (GPs) and dermatologists in the Netherlands.MethodsA qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 35 publications
2
18
0
1
Order By: Relevance
“…Nowadays, choosing an appropriate and individualized intervention often largely depends on the knowledge, expertise, and preference of the practitioner as well as reimbursement status and may be insufficiently aligned with the individual desire of the patient [22,23]. In a recent qualitative study among physicians, cryosurgery was cited as the predominant therapy because other forms of therapy were little known or because there was uncertainty about their use [24]. Nevertheless, most dermatologists in this qualitative survey stated that they were aiming for guideline-based therapy, which was also an important motivation for patients in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, choosing an appropriate and individualized intervention often largely depends on the knowledge, expertise, and preference of the practitioner as well as reimbursement status and may be insufficiently aligned with the individual desire of the patient [22,23]. In a recent qualitative study among physicians, cryosurgery was cited as the predominant therapy because other forms of therapy were little known or because there was uncertainty about their use [24]. Nevertheless, most dermatologists in this qualitative survey stated that they were aiming for guideline-based therapy, which was also an important motivation for patients in our study.…”
Section: Discussionmentioning
confidence: 99%
“…For a user checking the skin lesions with this SA, it may prove difficult to evaluate all relevant skin lesions, as lay users may not know which lesions could be dangerous and/or which the user cannot see (namely for users taking an image without a partner and/or if the lesions are located in places which are hard to reach). On the other hand, this may also occur in current clinical practice as previous studies suggested GPs usually do not perform a full‐body skin examination …”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, this may also occur in current clinical practice as previous studies suggested GPs usually do not perform a full-body skin examination. 20,21 These risks are mitigated by the SA in several ways. First, every pair of image and corresponding risk rating gets a quality control by a dermatologist.…”
Section: Discussionmentioning
confidence: 99%
“… 3 A Dutch qualitative study highlighted that some primary care clinicians’ principal approach to managing AK was treatment with cryosurgery, or referral to secondary care with patient-driven follow-up care. 4 This article aims to inform GPs on the management of AK based on the British Association of Dermatologists (BAD) guidelines, the authors’ opinions on effective virtual consultations on AK, and when to refer patients to secondary care.…”
Section: Introductionmentioning
confidence: 99%